Korelasi Antara Kompetensi Mengajar Guru Dengan Motivasi Belajar Siswa Di SMP Negeri 1 Alas Kabupaten Sumbawa - Afifuddin Afifuddin; I Made Widnya; Mashap Hanafi (Jurnal Eduforia: Jurnal Penelitian dan Pengembangan Pendidikan, 2026)
The problem formulation in this study is Is There a Positive Correlation Between Teachers' Teaching Competence and Students' Learning Motivation at SMP Negeri 1 Alas, Sumbawa Regency in the 2010/2011 Academic Year?. While the objective to be achieved in this study is to find out whether there is a positive correlation between teachers' teaching competence and students' learning motivation at SMP Negeri 1 Alas, Sumbawa Regency in the 2010/2011 Academic Year. To obtain research data, the data collection technique used is the questionnaire method as the main method and the observation method and document recording method as complementary methods. Furthermore, in utilizing the data to answer the truth and falsity of the proposed research hypothesis, the data analysis method used is the statistical analysis method with the product moment correlation coefficient formula. Based on the results of the data analysis in this study, the calculated r value was obtained at 0.709, then this value was consulted with the r table value of the product moment at a significance level of 5% with N = 36, obtained a value of 0.329. This fact shows that the calculated r is greater than the r table or 0.709 > 0.329, so the results of the data analysis in this study are declared significant. Thus, it can be concluded that “There is a positive correlation between teacher teaching competence and student learning motivation at SMP Negeri 1 Alas, Sumbawa Regency in the 2010/2011 academic year.